Excision and Circularization of Integrative Conjugative Element Tn5253 of Streptococcus pneumoniae - Santoro, Francesco; Romeo, Alessandra; Pozzi, Gianni; Iannelli, Francesco (Frontiers in Microbiology, 2018)
The Integrative Conjugative Element (ICE) Tn5253 of Streptococcus pneumoniae, conferring resistance to tetracycline and chloramphenicol, was found integrated at a 83-bp specific target site (attB) located in the rbgA gene of the pneumococcal chromosome. PCR analysis of Tn5253-carrying strains showed evidence of precise excision of Tn5253 from the pneumococcal chromosome with production of (i) circular forms of the ICE in which the ends were joined by a 84-bp sequence (attTn), and (ii) reconstituted chromosomal attB. When integrated into the chromosome, Tn5253 was flanked by attL, identical to attB, and attR, identical to attTn. Circular forms of Tn5253 were present at a concentration of 3.8 x 10-4 copies per chromosome, whereas reconstituted attB sites were at 3.0 x 10-4 copies per chromosome. Deletion of int-xis of Tn5253 abolished production of circular forms (<7.1 x 10-6 copies per chromosome) and was associated to the lack of Tn5253 conjugal transfer suggesting as expected that Tn5253 circular form acts as a conjugation intermediate.